2013
DOI: 10.3402/tellusb.v65i0.20197
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate and chloride aerosols during Holocene and last glacial periods preserved in the Talos Dome Ice Core, a peripheral region of Antarctica

Abstract: A B S T R A C T Antarctic ice cores preserve the record of past aerosols, an important proxy of past atmospheric chemistry. Here we present the aerosol compositions of sulphate and chloride particles in the Talos Dome (TD) ice core from the Holocene and Last Glacial Period. We find that the main salt types of both periods are NaCl, Na 2 SO 4 and CaSO 4 , indicating that TD ice contains relatively abundant sea salt (NaCl) from marine primary particles. By evaluating the molar ratio of NaCl to Na 2 SO 4 , we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…We classify the measured particles into four categories: "terrestrial dust," "sea salts," "mixture of terrestrial dust and sea salts," and "others/unknown," according to the combinations of detected elements, which are consistent with previous works for the DF, Talos Dome, and NEEM (Greenland) ice cores (Iizuka et al, 2009;Iizuka, Tsuchimoto, et al, 2012;Iizuka, Uemura, et al, 2012;Iizuka et al, 2013Iizuka et al, , 2016Oyabu et al, 2014Oyabu et al, , 2015; Figure 2). Below, we describe the typical particle compositions for each classification and discuss the uncertainties associated with possible misclassifications.…”
Section: Chemical Constituents Of Observed Particlessupporting
confidence: 83%
“…We classify the measured particles into four categories: "terrestrial dust," "sea salts," "mixture of terrestrial dust and sea salts," and "others/unknown," according to the combinations of detected elements, which are consistent with previous works for the DF, Talos Dome, and NEEM (Greenland) ice cores (Iizuka et al, 2009;Iizuka, Tsuchimoto, et al, 2012;Iizuka, Uemura, et al, 2012;Iizuka et al, 2013Iizuka et al, , 2016Oyabu et al, 2014Oyabu et al, , 2015; Figure 2). Below, we describe the typical particle compositions for each classification and discuss the uncertainties associated with possible misclassifications.…”
Section: Chemical Constituents Of Observed Particlessupporting
confidence: 83%
“…For salt concentrations, both the combination sublimationÁEDS method and the IDM method have a close relationship at depths from the surface snow to 4-m depth in the Dome Fuji region (Iizuka et al, 2012b). However, the relation is less close for Holocene ice of the Talos Dome ice core (Iizuka et al, 2013), which was drilled in a coastal area (Delmonte et al, 2010;Stenni et al, 2011). Specifically, the particles in the Talos Dome ice contain a lot of NaCl according to the sublimationÁEDS method.…”
Section: Introductionmentioning
confidence: 99%
“…Another area with this same issue is the Talos Dome site. Holocene ice at Talos Dome has a certain amount of NaCl yet is mismatched with the IDM (Iizuka et al, 2013 does not form NaCl. Similarly, Holocene ice in the Dome Fuji ice core has negligible NaCl, yet closely matches the IDM (Iizuka et al, 2012a(Iizuka et al, , 2012bOyabu et al, 2014).…”
Section: Sea-salt Modification Of Single Particles From Coastal To Inmentioning
confidence: 99%
“…Using this method, Iizuka et al . [, ] showed that sea salt in Talos Dome, a peripheral dome, remains a primary aerosol as NaCl during warm periods, whereas more than 90% of the sea salt in Dome Fuji came from a secondary aerosol as Na 2 SO 4 . With the same method, Iizuka et al .…”
Section: Introductionmentioning
confidence: 99%